The use of Rapid Assessment Methodology to Compliment Existing National Assessment/Surveillance System : A Study among Injecting Drug Users in Kepala Batas, Penang, Malaysia - Vicknasingam, B.; Navaratnam, V. (2005)
The study aims to show how data from a rapid assessment study can compliment data produced by the existing National Drug Information (NADI) system. Qualitative data gathering techniques was used and the WHO guide for conduction rapid assessment among injecting drug users was used as a guide. We used and inductive research strategy using the principles of triangulation. Results from the rapid assessment showed us how specific information provided by the rapid assessment include information about the use of heroin with other substances, the context in which risky injecting practices are being practiced (sharing injecting paraphernalia but not needles), the reasons for increase in frequency of injecting, the price of drugs, the types of injecting networks, context of sexual behavior, information regarding the health and social consequences of drug use are needed to understand the problem of substance abuse more effectively. We suggest the current NADI system need to include more socio-behavioral and health related variables in its database in order to understand particularly the substance abuse HIV/AIDS relationship